2022
DOI: 10.3389/fphar.2022.941656
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of immune infiltration in entorhinal cortex of patients with Alzheimerʼs disease

Abstract: Alzheimer’s disease (AD) is one of the most common neurodegenerative diseases and manifests as progressive memory loss and cognitive dysfunction. Neuroinflammation plays an important role in the development of Alzheimer’s disease and anti-inflammatory drugs reduce the risk of the disease. However, the immune microenvironment in the brains of patients with Alzheimer’s disease remains unclear, and the mechanisms by which anti-inflammatory drugs improve Alzheimer’s disease have not been clearly elucidated. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…We also found evidence underlying the numerical correlation between immune cell infiltrates in HTS, such as CD4 T cells (memory and resting) and CD8 T cells, resting and activated NK cells, and monocytes and macrophages M0. Some of these have been previously reported and others remain to be confirmed [ [21] , [22] , [23] ]. We compared the differences in immune infiltrating cell composition between HTS and normal tissues.…”
Section: Discussionmentioning
confidence: 79%
“…We also found evidence underlying the numerical correlation between immune cell infiltrates in HTS, such as CD4 T cells (memory and resting) and CD8 T cells, resting and activated NK cells, and monocytes and macrophages M0. Some of these have been previously reported and others remain to be confirmed [ [21] , [22] , [23] ]. We compared the differences in immune infiltrating cell composition between HTS and normal tissues.…”
Section: Discussionmentioning
confidence: 79%
“…We speculate that neuroin ammatory processes are a common booster of multiple pathologies and are de ned by brain aging. Other authors have demonstrated a varied in ltration of immune cells in the brain in Alzheimer's disease but its pathology implication is still unknown [45].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that some specific immune cells in brain tissue, including Treg cells, activated NK cells, and neutrophils, were significantly more or less abundant in patients with AD than in healthy controls (Hu and Wang, 2021), which is consistent with the results of this study. The infiltration levels of some immune cells, such as pDCs, macrophages, and basophils, were altered in the brain tissue samples of PD and AD patients compared to healthy controls (Qian et al, 2022;Zhang et al, 2022). The potential reasons for this were that the brain tissue samples were derived from different regions and that the pathological mechanisms of these two diseases are not completely the same.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Alzheimer’s disease (AD), the most common neurodegenerative disease, is also closely related to immune infiltration ( Hu and Wang, 2021 ; Qian et al, 2022 ; Zhang et al, 2022 ). A previous study revealed that some specific immune cells in brain tissue, including Treg cells, activated NK cells, and neutrophils, were significantly more or less abundant in patients with AD than in healthy controls ( Hu and Wang, 2021 ), which is consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%